Implementasi Pendidikan Akhlak dalam Kegiatan Harian Santri di Pondok Pesantren - Rifald Rizal; Nur Aisyah Zulkifli (STKIP Subang, 2025)
This study aims to describe and analyze the implementation of moral education (ta’dīb) in the daily routines of students at Pondok Pesantren Darul Hadits Al-Aidarusiyah. Moral education is viewed as the core of personality formation in Islamic pedagogy; therefore, pesantren serve as a strategic environment for the internalization of moral values through habituation, exemplary conduct, disciplinary systems, and spiritual training integrated throughout 24-hour activities. Employing a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews with the kyai, teachers, and students, as well as documentation analysis of the curriculum, daily schedules, and institutional regulations. Data were analyzed using Miles, Huberman, and Saldana’s interactive model, while credibility was ensured through source and methodological triangulation. The findings indicate that moral education in this pesantren is implemented comprehensively, systematically, and consistently across all dimensions of students’ daily lives. Moral values are not delivered as an independent subject; rather, they are embedded in worship practices, learning activities, social interactions, cleanliness routines, and disciplinary mechanisms. Triangulated data reveal strong coherence between planning, implementation, and evaluation, forming a structured and accountable moral development system. Four major determinants underpin the effectiveness of moral education: the holistic integration of moral values, the exemplary role of kyai and teachers, the controlled learning environment, and well-organized management structures. This study concludes that the pesantren’s model of moral education provides a valuable reference for other educational institutions seeking to develop comprehensive, effective, and sustainable character education systems.